Genotype × herbivore effect on leaf litter decomposition in Betula Pendula saplings: ecological and evolutionary consequences and the role of secondary metabolites. - Tarja Silfver; Ulla Paaso; Mira Rasehorn; Matti Rousi; Juha Mikola (PLoS ONE, 2015)
Plant genetic variation and herbivores can both influence ecosystem functioning by affecting the quantity and quality of leaf litter. Few studies have, however, investigated the effects of herbivore load on litter decomposition at plant genotype level. We reduced insect herbivory using an insecticide on one half of field-grown Betula Pendula saplings of 17 genotypes, representing random intrapopulation genetic variation, and allowed insects to naturally colonize the other half. We hypothesized that due to induced herbivore defence, saplings under natural herbivory produce litter of higher concentrations of secondary metabolites (terpenes and soluble phenolics) and have slower litter decomposition rate than saplings under reduced herbivory. We found that leaf damage was 89 and 53% lower in the insecticide treated saplings in the summer and autumn surveys, respectively, which led to 73% higher litter production. Litter decomposition rate was also affected by herbivore load, but the effect varied from positive to negative among genotypes and added up to an insignificant net effect at the population level. In contrast to our hypothesis, concentrations of terpenes and soluble phenolics were higher under reduced than natural herbivory. Those genotypes, whose leaves were most injured by herbivores, produced litter of lowest mass loss, but unlike we expected, the concentrations of terpenes and soluble phenolics were not linked to either leaf damage or litter decomposition. Our results show that (1) the genetic and herbivore effects on B. pendula litter decomposition are not mediated through variation in terpene or soluble phenolic concentrations and suggest that (2) the presumably higher insect herbivore pressure in the future warmer climate will not, at the ecological time scale, affect the mean decomposition rate in genetically diverse B. pendula populations. However, (3) due to the significant genetic variation in the response of decomposition to herbivory, evolutionary changes in mean decomposition rate are possible.